(untitled) (Global Journal of Computer Science and Technology, 2022)
Annotation- This article introduces an automated system for evaluating startups in the field of Software Engineering It outlines the system s components including database management expert assessments and project viability estimation The article also presents a conceptual database model and discusses the user interface for assessment calculations The system is designed to enhance the evaluation of Software Engineering startups and holds potential applications in various scenarios